HGG-12. A CASE OF PEDIATRIC SPINAL HIGH-GRADE GLIOMA WITH NTRK1 GENE FUSION. (4th December 2020) - Morisako, Tamaki; Umebayashi, Daisuke; Kamata, Kazuaki; Yamamoto, Hiroyuki; Yamanaka, Takumi; Takeuchi, Hayato; Takahashi, Yoshinobu; Tatsuzawa, Kazunori; Miyachi, Mitsuru; Yagyu, Shigeki; Iehara, Tomoko; Hosoi, Hajime; et al.
Abstract: INTRODUCTION: Tumors arising from the spinal cord are uncommon, especially high-grade tumors in pediatric patients. We report a case of high-grade glioma in the spinal cord harboring NTRK1 gene fusion, who received effective entrectinib therapy. CASE REPORT: A 5-year-old boy presented right hemiparesis and MR imaging revealed an intramedullary enhancing mass at the vertebral body level between C3 and Th1. He underwent microsurgical partial resection and the histological diagnosis was low-grade astrocytoma. After the first-line chemotherapy with vincristine and carboplatin, his right hemiparesis deteriorated and recurrent MR imaging showed growth of the tumor. He underwent microsurgical partial resection again and the histological examination was high-grade glioma with endothelial proliferation and necrosis. The chemoradiotherapy with temozolomide and focal irradiation of 50.4 Gy were given, and his neurological symptom slightly improved. One month later, he presented respiratory disturbance and required assisted ventilation with tracheostomy. MR imaging showed tumor progression invading upward to medulla oblongata. NTRK1 gene fusion was detected in the previous surgical specimen by a gene panel testing, and he received entrectinib, a potent inhibitor of tropomyosin receptor kinase (TRK). Since then, no tumor progression has been demonstrated for several months by MRI and he has been stable neurologically. CONCLUSION: High-grade spinal cord tumors are rare and effective treatment strategies have not been addressed. Although the frequency of the gene fusion is very low in pediatric gliomas, identification of the driver gene aberration like in this case by a gene panel can provide potential targeted therapies for selected patients.